Evaluation of leguminous vegetables as intercrops in pruned fields of jasmine (Jasminum sambac Ait.) - Manivannan, S Kamalakannan, M Lakshminarayanan, K Haripriya, K (Journal of Spices and Aromatic Crops, 2005)
Investigations on intercropping of leguminous vegetables in a pruned field of jasmine (Jasminum sambac) carried out in a farmer’s field at Keezakundalapadi (Cuddalore District, Tamil Nadu), indicated that intercropping pruned jasmine with double rows of vegetable cowpea (Vigna unguiculata) fetched the highest equivalent yield of jasmine (5,393 kg ha-I), land equivalent ratio (1.99), net returns (Rs. 1,44,113 ha-I) and benefit-cost ratio (3:1).